Anton Boisen: A Portrait - Kramp, Joseph M. (Journal of religion and health, 2012)
This psychobiographical essay aims to shift Boisen scholarship from a focus on his disputed psychiatric diagnosis to a more inclusive investigation of the disparate aspects of his personality. I conclude that Boisen's central personality trait was a brand of loquacity that lacked substancespecifically the substance of his deepest secrets. This caused a kind of chronic frustration in his relations with others and, I argue, led to his chronic, psychotic state of being. Additionally, I argue that Boisen's psychosis and religious practice worked together to sustain his psychological regression.